Next-generation sequencing diagnostics of bacteremia in pediatric sepsis - Schmoch, Thomas; Westhoff, Jens; Decker, Sebastian; Skarabis, Annabell; Hoffmann, Georg F.; Dohna-Schwake, Christian; Felderhoff-Müser, Ursula; Skolik, Caroline; Feißt, Manuel; Klose, Christina; Bruckner, Thomas; Luntz, Steffen P.; et al. (Medicine, 2021)
Introduction: - Sepsis and septic shock are the most severe forms of infection affecting predominantly elderly people, preterm and term neonates, and young infants. Even in high-income countries sepsis causes about 8% of admissions to pediatric intensive care units (PICUs). Early diagnosis, rapid anti-infective treatment, and prompt hemodynamic stabilization are crucial for patient survival. In this context, it is essential to identify the causative pathogen as soon as possible to optimize antimicrobial treatment. To date, culture-based diagnostic procedures (e.g., blood cultures) represent the standard of care. However, they have 2 major problems: on the one hand, in the case of very small sample volumes (and thus usually in children), they are not sufficiently sensitive. On the other hand, with a time-to-result of 2 to 5 days, blood cultures need a relatively long time for the anti-infective therapy to be calculated. To overcome these problems, culture-independent molecular diagnostic procedures such as unbiased sequence analysis of circulating cell-free DNA (cfDNA) from plasma samples of septic patients by next-generation sequencing (NGS) have been tested successfully in adult septic patients. However, these results still need to be transferred to the pediatric setting. - Methods: - The Next GeneSiPS-Trial is a prospective, observational, non-interventional, multicenter study used to assess the diagnostic performance of an NGS-based approach for the identification of causative pathogens in (preterm and term) neonates (d1-d28, n = 50), infants (d29 to <1 yr, n = 50), and toddlers (1 yr to <5 yr, n = 50) with suspected or proven severe sepsis or septic shock (according to the pediatric sepsis definition) by the use of the quantitative sepsis indicating quantifier (SIQ) score in comparison to standard of care (culture-based) microbiological diagnostics. Potential changes in anti-infective treatment regimens based on these NGS results will be estimated retrospectively by a panel of 3 independent clinical specialists. - Discussion: - Neonates, infants, and young children are significantly affected by sepsis. Fast and more sensitive diagnostic approaches are urgently needed. This prospective, observational, non-interventional, multicenter study seeks to evaluate an NGS-based approach in critically ill children suffering from sepsis. - Trial registration: - DRKS-ID: DRKS00015705 (registered October 24, 2018). https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00015705